2014
DOI: 10.1371/journal.pone.0107675
|View full text |Cite|
|
Sign up to set email alerts
|

Genital Human Papillomavirus Infection among Women in Bangladesh: Findings from a Population-Based Survey

Abstract: BackgroundThere has been no population-based study on human papillomavirus (HPV) prevalence or its genotypes in Bangladesh; a country eligible for GAVI funding for HPV vaccine.MethodsWe used baseline survey data of a prospective cohort study that was conducted in one urban and one rural area of Bangladesh. A total of 997 urban and 905 rural married women, aged 13 to 64 years, were enrolled in the baseline during July-December, 2011. Information was collected on socio-demographic characteristics and potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 48 publications
6
39
3
1
Order By: Relevance
“…All CIN grade 2 and 3 cases were positive for HPV while >50% was positive in CIN1. The rate of HPV infection was significantly low in chronic cervicitis (18.2%) but it was comparatively higher than that in women with normal cervical cytology [12]. Studies in different countries of Africa reported similar high rate of HPV infection in different grade of CIN [6].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…All CIN grade 2 and 3 cases were positive for HPV while >50% was positive in CIN1. The rate of HPV infection was significantly low in chronic cervicitis (18.2%) but it was comparatively higher than that in women with normal cervical cytology [12]. Studies in different countries of Africa reported similar high rate of HPV infection in different grade of CIN [6].…”
Section: Discussionmentioning
confidence: 79%
“…A previous study in Bangladesh has reported the presence of high risk HPV type (16, 18, 31 and 45) in about 56% of women with high risk behavior [13]. Similarly, a population based study in Bangladesh also found the prevalence of high risk HPV types among women with normal cytology [12].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These studies show that with literacy, better adoption of family planning practices and genital hygiene a reduction in HPV infection is achievable. Perdoor village in Udupi district shows a higher female literacy rate and better standards of living compared to the rest of India (Nair et al, 2000). Prevalence study carried out in North India found higher prevalence among rural women following non vegetarian diet and using homemade pads during menstruation (Srivastava et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…Multiple sexual partners increase the risk of incident as well as persistent HPV infections (Mollers et al, 2013). Women with 4 or more sexual partners were almost four times more at risk of having any HPV infection compared to women with single partner (Nahar et al, 2014). The causal association of HPV with cervical cancer is well accepted and the incidence of cervical cancer cases can be related with HPV prevalence in that area.…”
Section: Discussionmentioning
confidence: 99%